Two cases of 17α-hydroxylase/17,20-lyase deficiency caused by the CYP17A1 mutation - Hae In Lee; Ahreum Kwon; Jung Hwan Suh; Han Saem Choi; Kyung Chul Song; Hyun Wook Chae; Ho-Seong Kim (Korean Society of Pediatric Endocrinology, 2021)
17α-hydroxylase/17,20-lyase deficiency, caused by mutations in the cytochrome P450 family 17 subfamily A member 1 gene (CYP17A1), is an extremely rare form of congenital adrenal hyperplasia that is characterized by diverse phenotypes resulting from specific mutations. Here, we report 2 phenotypic females with 17α-hydroxylase/17,20-lyase deficiency: one with the 46,XX karyotype presenting primary amenorrhea and sexual infantilism, and the other with the 46,XY karyotype presenting a disorder of sexual development. In both cases, the serum levels of adrenocorticotropic hormone, 11-deoxycorticosterone, and gonadotropin were elevated, whereas the levels of testosterone and dehydroepiandrosterone were reduced. Next-generation sequencing revealed one patient with compound heterozygosity for p.Trp17Ter (c.51G>A) and p.His373Leu (c.1118A>T), and the other with homozygosity for p.His373Leu (c.1118A>T). This report further describes 2 cases of 17α-hydroxylase/17,20-lyase deficiency in patients who harbored a p.His373Leu substitution, commonly found in Korean individuals, and presented diverse phenotypes.